Health technology assessment in Japan: a work in progress. (2nd April 2020) - Kamae, Isao; Thwaites, Rob; Hamada, Anna; Fernandez, Jovelle L.
Abstract: Background: In Japan, pharmacoeconomic requirements for list-price adjustment were institutionalized in April 2019 following provisional implementation of a new Health Technology Assessment (HTA) program 2016–2019. Since April 2019, submission of cost-effectiveness evidence to the Central Social Insurance Medical Council (Chuikyo) as part of the Japanese Ministry of Health, Labour, and Welfare has been mandatory for selected pharmaceuticals and medical devices. Methods: Based on a review of publications and commentaries since April 2019, together with views from a group of experts on key issues to be addressed, this report provides an update on recent HTA developments and key challenges still to be addressed. Results and Discussion: Japan's new HTA program is a first step toward development of a universal healthcare system that can be sustainable for many years into the future. Currently, Japan's HTA program requires provision of incremental cost-effectiveness ratios (ICERs) as evidence, with quality-adjusted life years as the preferred outcome measure. Prices can be adjusted both upward and downward according to the degree of the ICER estimate. Japan is the first country to have adopted an algorithmic method for "ICER-based" pricing; however, HTA measures that extend beyond a single ICER estimate are needed to take full advantage of HTA in the future. In particular, generation of evidence of value should support changes to the healthcare system so that incentives for innovation are not diminished while industry and government are not overburdened by the generation or assessment of evidence. There is a need to ensure scientifically sound HTA expertise across all sectors in Japan, and therefore enhancement of HTA literacy and capability among healthcare professionals, academia, government, and industry should be a priority.